Karakteristik Pekerja Industri Tekstil yang Terdiagnosis Kanker di Purwakarta - Tiara Oktaviani; Riri Risanti (Jurnal Riset Kedokteran, 2022)
Abstract. The results from a survey conducted by the International Labor Organization showed that the highest prevalence of occupational causes of death was due to cancer, which was 8%. Cancer is an uncontrolled growth of cells following the invasion of surrounding tissues and spread to the other parts of the body. This diseases are known to be related to the work environment, one of which is the textile industry because they are exposed to carcinogenic substances. This study aims to find out the characteristics of cancer patients who were textile industry workers. They were categorized based on age, gender, and type of cancer diagnosed at Bayu Asih Hospital and Abdul Radjak Purwakarta Hospital in 2018-2019. This study used a descriptive observational method by looking at the medical record data of cancer patients at Bayu Asih Hospital and Abdul Radjak Purwakarta Hospital from January 2018 - December 2019 with a cross sectional design. The result it was found that the incidence of cancer in textile industry workers is higher in women 61.3% than men 38.7%. 46-55 years old 58.1%, 36-45 years old 35.5%, 36-45 years old 35.5% and the types of cancer are lung cancer 25.8%, breast cancer 22.6%, and skin cancer 12.9%. This shows that the the majority of textile industry workers diagnosed with cancer are female, aged 46-55 years, and the most common type of cancer is lung cancer. Abstrak. Hasil survey dari International Labour Organization menunjukkan bahwa prevalensi terbesar penyebab kematian yang berhubungan dengan pekerjaan disebabkan oleh kanker yaitu sebesar 8%. Kanker merupakan pertumbuhan sel yang tidak terkontrol diikuti proses invasi ke jaringan sekitar dan penyebaran ke bagian tubuh yang lain. Penyakit ini diketahui berhubungan dengan lingkungan kerja salah satunya yaitu industri tekstil karena terpapar oleh zat-zat karsinogenik. Penelitian ini bertujuan untuk mengetahui karakteristik pasien kanker yang bekerja di industri tekstil berdasarkan usia, jenis kelamin, dan jenis kanker yang terdiagnosis di RSUD Bayu Asih dan RS Abdul Radjak Purwakarta tahun 2018-2019. Penelitian ini menggunakan metode observasional deskriptif dengan melihat data rekam medis pasien kanker di RSUD Bayu Asih dan RS Abdul Radjak Purwakarta selama periode bulan Januari 2018-Desember 2019 dengan rancangan cross-sectional. Didapatkan kejadian kanker pada pekerja industri tekstil lebih tinggi pada perempuan 61.3% daripada laki-laki 38.7%. Berusia 46-55 tahun 58.1%, usia 36-45 tahun 35.5%, usia 36-45 tahun 35.5% dan jenis kankernya yaitu kanker paru-paru 25.8%, kanker payudara 22.6%, dan kanker kulit 12.9%. Kesimpulan penelitian ini adalah mayoritas pekerja industri tekstil yang terdiagnosis kanker berjenis kelamin perempuan, berusia 46-55 tahun, dan jenis kanker yang paling banyak adalah kanker paru.